Genetic Variability Based on Tandem Repeat Numbers in a Genomic Locus of ‘Candidatus Liberibacter asiaticus’ Prevalent in North East India - Yanglem Herojit Singh; Susheel Kumar Sharma; Bireswar Sinha; Virendra Kumar Baranwal; N. Bidyananda Singh; Ngathem Taibangnganbi Chanu; Subhra S. Roy; Meraj A. Ansari; Arati Ningombam; Ph. Sobita Devi; Ashis Kumar Das; Salvinder Singh; et al. (The Plant Pathology Journal, 2019)
The genetic variability of ‘Candidatus Liberibacter asiaticus’ (CLas) population associated with huanglongbing (HLB) disease of citrus in North Eastern (NE) region of India, a geographically locked region, and home for the diversity of many citrus species was analyzed on the basis of tandem repeat numbers (TRN) in variable CLIBASIA_01645 genomic loci. Fifty-five CLas strains sampled from different groves of NE Hill (NEH) region of India were in single amplicon group, but there was remarkable genetic variability in TRNs. The TRN in HLB-associated CLas strains varied from 0-21 and two novel repeat motifs were also identified. Among the NE population of CLas, TRN5 and TRN9 were most frequent (total frequency of 36.36%) followed by TRN4 (14.55%) and TRN6, TNR7 with a frequency of 12.73% each. Class II type CLas genotypes (5 < TRN ≤ 10) had highest prevalence (frequency of 60.00%) in the samples characterized in present study. Class I (TRN ≤ 5) genotypes were second highest prevalent (29.09%) in the NEH region. Further analysis of genetic diversity parameters using Nei's measure (H value) indicated wide genetic diversity in the CLas strains of NE India (H value of 0.58-0.86). Manipur CLas strains had highest genetic variability (0.86) as compared to Eastern, Southern and Central India. The R10 values (TRN ≤ 10/TRN > 10) of NE CLas population was 10.43 (73/7), higher from other regions of India. Present study conclusively reported the occurrence of high genetic variability in TRN of CLas population in North East Indian citrus groves which have evolved to adapt to the specific ecological niche.